2014
DOI: 10.1111/cas.12404
|View full text |Cite
|
Sign up to set email alerts
|

LIM protein JUB promotes epithelial–mesenchymal transition in colorectal cancer

Abstract: Metastasis is the leading cause of cancer-related death in almost all types of cancers, including colorectal cancer (CRC). Metastasis is a complex, multistep, dynamic biological event, and epithelial–mesenchymal transition (EMT) is a critical process during the cascade. Ajuba family proteins are LIM domain-containing proteins and are reported to be transcription repressors regulating different kinds of physiological processes. However, the expression and pathological roles of Ajuba family proteins in tumors, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 33 publications
5
28
1
Order By: Relevance
“…A previous report showed that Ajuba was up-regulated in colon cancer cell lines and tumors (22). We further analyzed the expression of Ajuba in published data and confirmed that the mRNA levels of Ajuba were significantly increased in colon tumors compared with normal colon (Fig.…”
Section: Ajuba Phosphorylation Occurs During Normal Mitosis-tosupporting
confidence: 78%
See 3 more Smart Citations
“…A previous report showed that Ajuba was up-regulated in colon cancer cell lines and tumors (22). We further analyzed the expression of Ajuba in published data and confirmed that the mRNA levels of Ajuba were significantly increased in colon tumors compared with normal colon (Fig.…”
Section: Ajuba Phosphorylation Occurs During Normal Mitosis-tosupporting
confidence: 78%
“…Interestingly, whereas these studies clearly showed that Ajuba promotes cell proliferation, Ajuba was shown to suppress malignant mesothelioma cell proliferation (23), suggesting a cell type-specific role of Ajuba in cancer cells. In line with a role of Ajuba in cancer, recent large scale genomic studies found that the Ajuba gene is mutated in 7% of esophageal squamous cell carcinomas (24,25) and Ajuba is overexpressed in colon cancer patients (22). Our current study further demonstrates that mitotic phosphorylation of Ajuba by CDK1 is critical for its biological function, suggesting that there is a link between the role of Ajuba in cancer and its mitotic regulation and that Ajuba may exert its role in cancer through deregulation in mitosis.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Furthermore, the LIM protein Ajuba (41,42), a known negative regulator of the Hippo pathway, via inhibition of LATS (large tumor suppressor kinase 1) kinase (43)(44)(45), that interacts with catenin family members at cell-cell contacts (adherens junctions) and with cadherin family members (46)(47)(48), has been found to promote the epithelial-to-mesenchymal transition in colorectal cancers (49), and its lentivirus transduction into malignant mesothelioma suppresses their proliferation via modulation of the Hippo pathway (50). In addition, findings demonstrating increased expression levels of YAP and survivin and decreased LATS activity in gastric and hepatocellular carcinomas (51,52) are consistent with Ajuba expression and localization possibly being an important regulator of the Hippo pathway in endothelia.…”
Section: Discussionmentioning
confidence: 99%